Prevalence of sexual violence and associated factors among women attending antenatal care in Debre Markos at public health institutions in north-west Ethiopia, 2021 - Abegaz, Marta Yimam; Muche, Haymanot Alem; Aynalem, Getie Lake; Anteneh, Tazeb Alemu; Tibebu, Nebyu Solomon; Gedef, Getachew Muluye; Mengstie, Aregash Sitot (Frontiers in Global Women's Health, 2023)
Background: Sexual violence refers to being forced, coerced, or threatened to perform any unwanted sexual act. Sexual violence during pregnancy is a public health crisis because it affects both mother and fetus. Knowing the prevalence of sexual violence during pregnancy helps policymakers the extent of the problem that can be considered the first step toward the implementation of interventions for prevention and treatment. This study was done to determine the prevalence of sexual violence and its associated factor during pregnancy in public hospitals in Debre Markos town. Methods: An institution-based cross-sectional study was conducted among 306 pregnant women. A systematic sampling procedure was used to select study participants. Data were collected using a structured, pre-tested, and, interviewer-administered questionnaire. Both bi-variable and multivariable logistic regression analyses were undertaken to identify significantly associated variables with sexual violence. The adjusted odds ratio (AOR) with its 95% confidence interval (CI) at a p-value of ≤ 0.05 was used to claim statistical association. Result: About 304 respondents were interviewed making a response rate of 99.3 %. In this study, the overall prevalence of sexual violence among pregnant mothers during the current pregnancy was 19.4%. Husband had no formal education (AOR =4.401; 95%CI: 1.027, 18.862], pregnant mothers who had no formal education AOR= 6.1;95%CI:1.497-24.86 and being housewife AOR=4.831,95CI:1.351,17.269 were factors associated with sexual violence at 𝑝 value < 0.05 Conclusions and recommendations: In this study about one-fifth of the study participants experienced sexual violence during pregnancy. To decrease sexual violence during pregnancy, increase awareness, and reduce the stigma, taboos, and misconceptions surrounding violence against women. Keywords: - Sexual violence, Pregnant, Antenatal care, Ethiopia